Teoria prawa Zygmunta Ziembińskiego - Kordela, Marzena (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2015)
Zygmunt Ziembiński was one of the most prominent theoreticians of law in Poland in the second half of the 20th century. He developed an original theory of law defined as a theory of legal phenomena, which covered both logical-linguistic as well as real aspects of law. The theory served as a base for the development of a unique so-called advanced normative conception of sources of law, one of the greatest achievements of theory of law in Poland. This conception encompasses all the indispensable elements of a coherent system of binding legal norms: 1) indication of a political justification (ideological assumptions) of the entire system of law; 2) pre-judgment of law-making competence of government agencies; 3) determination of the status of custom and precedent; 4) compilation of a catalogue of permissible interpretation rules; 5) compilation of a catalogue of permissible inferential rules (permissible rules of legal inferences); 6) compilation of a catalogue of permissible collision rules.
Theory of Law by Zygmunt Ziembiński
Keywords: theory of law; analytical philosophy; legal axiology; law; legal norm; competence norm; thetic norms; axiological norms; rational legislator; validation rules; rules of exegesis of law; interpretation rules; inference rules; collision rules; conventional acts